2017
DOI: 10.18632/oncotarget.18648
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol up-regulates miR-494-3p to suppress BMI1 expression and inhibits self-renewal of breast cancer stem/progenitor cells

Abstract: Hinokitiol (β-thujaplicin) is a tropolone-related compound that has anti-microbe, anti-inflammation, and anti-tumor effects. Cancer stem/progenitor cells (CSCs) are a subpopulation of cancer cells with tumor initiation, chemoresistant, and metastatic properties and have been considered the important therapeutic target in future cancer therapy. Previous studies reported that hinokitiol exhibits an anti-cancer activity against murine tumor cells through the induction of autophagy. The current research revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 45 publications
0
39
0
6
Order By: Relevance
“…The results implied that MEG3 could regulate the expression of miR-494-3p as a ceRNA. Zhou et al have previously reported that miR-494-3p can promote cell proliferation and tumor growth in breast cancer through targeted inhibiting TRIM21 expression 26 , and miR-494-3p has been found to inhibit self-renewal of breast cancer stem/progenitor cells 27 , indicating the important regulatory role of miR-494-3p in breast cancer. In the study, we inhibited the cell activity, migration and invasion abilities of breast cancer cells by overexpression of MEG3.…”
Section: Discussionmentioning
confidence: 99%
“…The results implied that MEG3 could regulate the expression of miR-494-3p as a ceRNA. Zhou et al have previously reported that miR-494-3p can promote cell proliferation and tumor growth in breast cancer through targeted inhibiting TRIM21 expression 26 , and miR-494-3p has been found to inhibit self-renewal of breast cancer stem/progenitor cells 27 , indicating the important regulatory role of miR-494-3p in breast cancer. In the study, we inhibited the cell activity, migration and invasion abilities of breast cancer cells by overexpression of MEG3.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of miR-494 has been reported in various cancers. However, the role of miR-494 in carcinogenesis is contradictory, including a tumor suppressor role [45,46] and an oncogenic role [47,48]. Zhan et al revealed that miR-494 can inhibit the progression and metastasis of breast carcinomas by targeting P21 (RAC1) activated kinase 1 [49].…”
Section: Discussionmentioning
confidence: 99%
“…As for cancer stemness, miR-494-3p was proven to target BMI1 and inhibit various features of cancer stemness in breast cancer. In addition, miR-494-3p expression was inversely correlated with patient survival [98]. MiR-494 also has been shown to influence the stemness properties of HCC by increasing various stemness genes, such as PROM1, Oct4 and Sox2, as well as ABCG2 transporter levels [99].…”
Section: Microrna-494mentioning
confidence: 99%